2013
DOI: 10.1016/j.jacc.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex on Risk Stratification With Stress Myocardial Perfusion Rb-82 Positron Emission Tomography

Abstract: Stress Rb-82 PET provides significant and clinically meaningful effective risk stratification of women and men, supporting this modality as an alternative to comparative imaging modalities. Rb-82 PET findings were particularly helpful at identifying high-risk, older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 51 publications
3
35
1
Order By: Relevance
“…This approach has now been successfully applied in a number of prognostic analyses using nuclear imaging. [3][4][5][6][7][8][9] Although most reports quantifying the overall NRI have reported that nuclear variables add considerably to the ability to accurately detect low-and high-risk individuals, in this issue of the journal, Koh and colleagues 7 reported intriguing results from a relatively large, singlecenter database of 6702 patients referred for exercise myocardial perfusion imaging (MPI) for either suspected or known coronary artery disease (CAD). This report provided a unique approach by formulating three models including the base comparator of a clinical model which was then compared to a model adding the Duke Treadmill Score (DTS), and then a third model adding the summed difference score and a categorical post-stress left ventricular ejection fraction variables.…”
Section: See Related Article Pp 366-378mentioning
confidence: 99%
See 3 more Smart Citations
“…This approach has now been successfully applied in a number of prognostic analyses using nuclear imaging. [3][4][5][6][7][8][9] Although most reports quantifying the overall NRI have reported that nuclear variables add considerably to the ability to accurately detect low-and high-risk individuals, in this issue of the journal, Koh and colleagues 7 reported intriguing results from a relatively large, singlecenter database of 6702 patients referred for exercise myocardial perfusion imaging (MPI) for either suspected or known coronary artery disease (CAD). This report provided a unique approach by formulating three models including the base comparator of a clinical model which was then compared to a model adding the Duke Treadmill Score (DTS), and then a third model adding the summed difference score and a categorical post-stress left ventricular ejection fraction variables.…”
Section: See Related Article Pp 366-378mentioning
confidence: 99%
“…Higher NRI calculations for stress PET imaging data estimating cardiac mortality have been reported for men (NRI: 0.17) and older women (NRI: 0.21). 6 7 report provided a unique approach by formulating three models including the base comparator of a clinical model compared to a model adding the DTS, and then a third model of MPI variables. This demonstrates the incremental value of adding the DTS or data derived from MPI to baseline clinical risk factors in risk assessment.…”
Section: See Related Article Pp 366-378mentioning
confidence: 99%
See 2 more Smart Citations
“…Besides having a more favorable radiation exposure profile [3], PET myocardial perfusion provide improved image contrast and allows for quantitative measurements of myocardial blood flow and coronary flow reserve. In addition, PET myocardial perfusion has a high diagnostic accuracy [4][5][6][7]. Important to realize is that the spatial resolution of PET images is directly related to the positron range.…”
Section: Introductionmentioning
confidence: 99%